(untitled) (Herald of the National Children’s Medical Center, 2025)
In recent years, the incidence of urolithiasis (UL) in early childhood children has been increasing. In this age group, the disease accounts for 20% of the total cases of UL. In early childhood, the disease is characterized by specific clinical courses and various complications. Identifying and analyzing etiological factors is of urgent importance for developing preventive measures.